Long-term adverse outcomes from neonatal circumcision reported in a survey of 1, 008 men: an overview of health and human rights implications*. Issue 2 (12th February 2017) - Hammond, Tim; Carmack, Adrienne
ABSTRACT: Amid growing bioethical and human rights concerns over non-therapeutic infant male circumcision, calls have been made to investigate long-term impacts on the men these infants eventually become. The present inquiry attempts to identify factors contributing to concerns of men claiming dissatisfaction with or ascribing harm from neonatal circumcision. This large sample size survey involved an online questionnaire with opportunities to upload photographic evidence. Respondents revealed wide-ranging unhealthy outcomes attributed to newborn circumcision. Survey results establish the existence of a considerable subset of circumcised men adversely affected by their circumcisions that warrants further controlled study. Empirical investigations alone, however, may be insufficient to definitively identify long-term effects of infant circumcision. As with non-therapeutic genital modifications of non-consenting female and intersex minors, responses are highly individualistic and cannot be predicted at the time they are imposed on children. Findings highlight important health and human rights implications resulting from infringements on the bodily integrity and future autonomy rights of boys, which may aid health care and human rights professionals in understanding this emerging vanguard of men who report suffering from circumcision. We recommend further research avenues, offer solutions to assist affected men, and suggest responses to reduce the future incidence of this problem.